2017
DOI: 10.1038/ejhg.2016.175
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption is associated with DNA methylation levels of human blood

Abstract: Beneficial health effects have been attributed to coffee consumption, but it is not yet known whether epigenetics may have a role in this process. Here we associate epigenome-wide DNA methylation levels to habitual coffee consumption from two studies with blood (2100 and 215 participants), and one with saliva samples (256 participants). Adjusting for age, gender, and blood cell composition, one CpG (cg21566642 near ALPPL2) surpassed genome-wide significance (P=3.7 × 10) and from among 10 additional CpGs signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…It is unlikely that PD status influenced the accuracy of reporting coffee/tea consumption; thus, we would expect non-differential misclassification that tends to bias estimates toward the null. Moreover, we have published a coffee EWAS study using the same samples [ 24 ], which was consistent with the literature on coffee and PD. For example, the estimated effect size for coffee consumption and PD risk for three additional cups of coffee per day (odds ratio [OR] 0.73, 95% confidence interval [CI] 0.58–0.92) in our study is consistent with the estimated effect size reported in a meta-analysis of 13 coffee and PD studies (OR 0.75, 95% CI 0.64–0.86) [ 25 ].…”
Section: Discussionsupporting
confidence: 84%
“…It is unlikely that PD status influenced the accuracy of reporting coffee/tea consumption; thus, we would expect non-differential misclassification that tends to bias estimates toward the null. Moreover, we have published a coffee EWAS study using the same samples [ 24 ], which was consistent with the literature on coffee and PD. For example, the estimated effect size for coffee consumption and PD risk for three additional cups of coffee per day (odds ratio [OR] 0.73, 95% confidence interval [CI] 0.58–0.92) in our study is consistent with the estimated effect size reported in a meta-analysis of 13 coffee and PD studies (OR 0.75, 95% CI 0.64–0.86) [ 25 ].…”
Section: Discussionsupporting
confidence: 84%
“…Other studies showed that dietary components can influence gene expression through epigenetic mechanisms 63 , 64 . Notably, methylation differences related to coffee consumption were observed only in women who never used menopausal hormone therapy (MHT) and suggest that coffee may affect DNA methylation levels in immune cells of the blood 65 . It is also suggested that oestrogen receptor alpha (ERα) may regulate gene expression partially via DNA methylation 66 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that habitual coffee consumption can alter DNA methylation sites in human genome. It revealed alterations in methylation status of CpG sites located near of 11 genes associated with habitual coffee consumption in peripheral blood mononuclear cells (Chuang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%